2022
DOI: 10.3390/cancers14040881
|View full text |Cite
|
Sign up to set email alerts
|

Development of Gene Expression-Based Random Forest Model for Predicting Neoadjuvant Chemotherapy Response in Triple-Negative Breast Cancer

Abstract: Neoadjuvant chemotherapy (NAC) response is an important indicator of patient survival in triple negative breast cancer (TNBC), but predicting chemosensitivity remains a challenge in clinical practice. We developed an 86-gene-based random forest (RF) classifier capable of predicting neoadjuvant chemotherapy response (pathological Complete Response (pCR) or Residual Disease (RD)) in TNBC patients. The performance of pCR classification of the proposed model was evaluated by Receiver Operating Characteristic (ROC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 91 publications
0
2
0
Order By: Relevance
“…However, ML models have recently been the subject of numerous research studies across various cancer types, including ovarian, thyroid, and breast cancer. [ 11 12 13 ] These studies demonstrate the potential of ML in predicting disease outcomes and identifying biomarkers for early diagnosis. Toth et al .…”
Section: Discussionmentioning
confidence: 88%
“…However, ML models have recently been the subject of numerous research studies across various cancer types, including ovarian, thyroid, and breast cancer. [ 11 12 13 ] These studies demonstrate the potential of ML in predicting disease outcomes and identifying biomarkers for early diagnosis. Toth et al .…”
Section: Discussionmentioning
confidence: 88%
“…Random forests can be used in the identification of putative disease‐related biomarkers. In a study, researchers employed Random Forest to find genes that were typically observed in individuals with breast cancer (Park & Yi, 2022). The algorithm discovered a group of genes linked to cancer development that may be employed as biomarkers for early identification and individualized therapy.…”
Section: Applications Of Deep and Machine Learning In Medical Fieldsmentioning
confidence: 99%